A memória das lutas ou o lugar do "DO": as artes marciais e a construção de um caminho oriental para a cultura corporal na cidade de São Paulo - Marta, Felipe Eduardo Ferreira (2009)
Currently, the eastern martial arts are a part of the corporal culture of the city of São Paulo. His practice is available as an opportunity to experience. In other words, anyone that desire easily can have access to those corporal practices originated at countries of the far east. But how that was possible? How an element of so different culture is able to be established in São Paulo? To try to answer those questions that, I wrote this work. Accordingly, this research was based on oral sources, bibliographic and documentary to investigate the process of introduction and spread of some of the most popular eastern martial arts practiced today in the city of São Paulo. Specifically on oral sources, I chose a strategy that focused masters immigrants from three countries: Japan, China (Hong Kong) and South Korea. The justification for such strategy resides in the fact of that are those the countries where originated some of the most popular eastern martial arts, currently practiced in the city of São Paulo. For analysis of the statements, were observed the annotations of Alessandro Portelli (1997), for whom the oral reports It is a document of present, in its shared responsibility by both the deponent as the researcher . As a result, it was observed that the introduction of oriental martial arts in most due to the migration of peoples of oriental origin, started in the early years of the twentieth century, and that the success in the work of dissemination of such practices should be the process of modernization, the perspective advocated by Norbert Elias (1994), to which they were submitted. This modernization is expressed in the adoption in their home countries and also in the receiving country, in Brazil, the labor standards of some body of European origin, with emphasis, accordingly, for the sport and gymnastics and also the methods by "control the potential violence" inherent in such practices. It was also noted that the period after World War II, more specifically in the 1960s and 1970s, represented a new moment in the dissemination of such practices in the city. Process that until then had been promoted by the exclusive work of the masters immigrants and that from that moment on, begin to benefit from the emergence of a breeding ground for these practices arise from increased visibility in the city, a phenomenon generated by the diffusion mass products of the entertainment industry relating to eastern martial arts. Finally, there was the role of a phenomenon that began for some of these practices even in the final years of the nineteenth century, in their home countries, but currently still in progress, making it a sport. Accordingly, with the help of the studies conducted by Pierre Bourdieu (1990, 1983) and Norbert Elias (1994, 1992), it was found that the unfolding of this process have been the responsible for a clash between the traditions of martial arts and oriental desires of those who are supporters of the process of modernization, Westernization and spotivization of these practices. Such situation has acted in the sense of become possible the association of the martial arts in a variety of ways. Senses that in some way seek satiate the desires of the actors involved in the life of martial arts, are the work of dissemination of the practice and are in its consumption